2023
DOI: 10.1111/ajes.12506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of healthy human capital and environmental regulation on green total factor productivity in China

Abstract: Environment affects the health of residents; to promote high‐quality economic development, their combined effect is crucial in measuring green total factor productivity (GTFP). Yet, scholars seldom consider the regulatory effect of the environment, spillover effect of healthy human capital, and synergistic effect between the environment and the health of residents. Using the panel threshold model and spatial Durbin model, along with the measurement of inter‐provincial GTFP from 2011 to 2019, we examine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They showed that command-and-control environmental regulation inhibited the growth of enterprise total factor productivity. Zheng and Chen [25] measured the interprovincial GTFP in China and showed that environmental regulation inhibited the increase in GTFP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that command-and-control environmental regulation inhibited the growth of enterprise total factor productivity. Zheng and Chen [25] measured the interprovincial GTFP in China and showed that environmental regulation inhibited the increase in GTFP.…”
Section: Literature Reviewmentioning
confidence: 99%